The Associations Between the Anorexic Readiness Syndrome, Familism, and Body Image Among Physically Active Girls - Ziółkowska, Beata; Ocalewski, Jarosław; Da̧browska, Aleksandra (Frontiers in Psychiatry, 2022)
Introduction: Anorexic Readiness Syndrome (ARS) is a construct useful in the selection of people showing a tendency to use restrictive diets and increased concentration on the body. The aim of the research was to verify the significance of the type of physical activity, body perception and familism for the development of ARS. The results of the research show that aesthetic sports and concentration on the body are risk factors for engaging in non-constructive eating behavior, and that familism plays an important role in mental health. Material and method: The research was carried in 2021 on a sample of 163 girls. It consisted of: 1) physically inactive girls, 3) physically active girls in disciplines other than aesthetic, 2) girls engaged in aesthetic physical activity. The study used: Anorexic Readiness Syndrome Questionnaire (ARS-12), Familism Scale (FS) and Body Image Avoidance Questionnaire (BIAQ). Results: The highest average ARS score was recorded in the group of girls engaged in aesthetic activity. A significant difference in the severity of ARS occurs between people who do not engage in activity and those who practice aesthetic activity. The severity of ARS rises as the difference between real and ideal body weight increases. People active in aesthetic disciplines who obtained a high score on the Respect scale (FS subscale) have a lower ARS score than those physically active in other disciplines who obtained low scores on the Respect scale. The higher the score on the Material success and achievement scale (FS), the greater the ARS intensity in all subgroups. The focus on eating and body weight and Clothing and appearance (BIAQ subscales) are relevant to the ARS and moderate the relationship between Material success (FS subscale) and anorexic readiness. Conclusions: People engaging in aesthetic physical activity are more likely to suffer from ARS. The family can certainly prevent a child from developing anorexic readiness by shaping a sense of community and family identity, a clear division of roles, limiting the importance of materialism and competition in raising children. The prevention of ARS should also focus on strengthening the realistic assessment of body parameters and their acceptance.